An extension of Broms' theory to unsaturated soils. (March 2023) - Lalicata, Leonardo Maria; Bruno, Agostino Walter; Gallipoli, Domenico
Abstract: This paper presents an analytical method to predict the horizontal capacity of piles in unsaturated soils. The method extends the well-known Broms approach to account for the combined effect of the groundwater table and the apparent cohesion of the unsaturated soil above it. Similar to the original formulation of Broms, the present method calculates the maximum horizontal force and bending moment that can be sustained by the pile for two different head fixities (i.e. free-head and restrained-head) as a function of non-dimensional parameters that depend on the geometry and flexural resistance of the pile (i.e. yielding moment), the soil resistance and the type of failure mechanism (i.e. short, intermediate or long pile). Compared to Broms' solution, the method introduces additional non-dimensional parameters that relate the water retention behaviour of the soil to the geometry of the pile. The proposed formulation accurately predicts the lateral capacity of piles as experimentally measured in previous works. Results confirm that consideration of the partially saturated state of the soil above the groundwater table is essential for a reliable estimate of the horizontal capacity of piles.